2020
DOI: 10.1021/acs.jafc.9b06304
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Exogenous Resveratrol on the Growth and Energy Metabolism of Zea mays and the Weed Ipomoea grandifolia

Abstract: An increase in crop competitiveness relative to weed interference has the potential to reduce crop yield losses. In this study, the effects of phytoalexin resveratrol were examined in Zea mays L. (corn) and in the weed species Ipomoea grandifolia (Dammer) O’Donell (morning glory). At a concentration range from 220 to 2200 μM resveratrol exerted a stimulus on Z. mays seedling growth that was more pronounced at low concentrations; in the weed species I. grandifolia, resveratrol exerted inhibitory action on seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
2
6
0
Order By: Relevance
“…Resveratrol did not significantly affect the lettuce seed germination, reproducing the observation of Mantovanelli et al (2020) in Z. mays and I. grandifolia. Similar results were also reported in radish seeds where resveratrol did not have intensive germination-stimulating properties, unlike protectors to ethanol seed sterilization treatment (Balanov et al 2021).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Resveratrol did not significantly affect the lettuce seed germination, reproducing the observation of Mantovanelli et al (2020) in Z. mays and I. grandifolia. Similar results were also reported in radish seeds where resveratrol did not have intensive germination-stimulating properties, unlike protectors to ethanol seed sterilization treatment (Balanov et al 2021).…”
Section: Discussionsupporting
confidence: 78%
“…Conversely, it significantly stimulated fresh and dry weight of the aerial part of lettuce, already at low concentrations, leaving unchanged the length and weight of the root system. This positive effect was already observed in maize seedlings, although only at 440 µM resveratrol concentration (Mantovanelli et al 2020).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The inhibition of cytochrome c oxidase was achieved by adding 1 mM KCN. Cyanide-resistant mitochondrial respiration was determined as the rate of oxygen uptake after the addition of KCN as inhibitor, assuming 100% as the rate of oxygen consumption by mitochondria in the oxidative phosphorylation state before the addition of the inhibitor [ 44 , 45 ]. The rate of succinate oxidation was expressed in nmol O 2 min −1 mg −1 protein.…”
Section: Methodsmentioning
confidence: 99%
“…So far, very few reports have reported the occurrence of phytotoxic damage induced by stilbenoids. Mantovanelli et al 117 argued that exogenous resveratrol ranging between 220 to 2200 μM (between 50−500 mg/L) served as a stimulus for Zea mays seedling growth, but also as an inhibitor of the growth of Ipomoea grandifolia weed, thereby supporting the use of exogenous resveratrol for crop protection. Another report by Sańchez-Goḿez et al 118 indicated nonphytotoxic effects of vine-shoot extracts on Lactuca sativa lettuce.…”
Section: Safety Aspects Of Stilbenoidsmentioning
confidence: 99%